PENINGKATAN KUALITAS PROSES PRODUKSI TAHU MENGGUNAKAN METODE FMEA DAN FTA (STUDI KASUS: PABRIK TAHU DN) - Fitriana, Rina; Sari, Indah Permata; Sukma, Indah Millia (Jurnal Teknologi Industri Pertanian, 2023)
DN Tofu Factory is a food industry for tofu products. The company’s main problem is a defect product in October-December 2021 with an average of 7.01%. The purpose of research was to reduce the failure of production in use of the methods of Failure Mode and Effect Analysis (FMEA) and Fault Tree Analysis (FTA). The result of DPMO (Defect per Million Opportunities) calculation is 17500 with a sigma level of 3.6084. Based on the FMEA calculations, two potential causes of failure from the highest perceived value of the RPN (Risk Priority Number), namely that workers do not use the full clothing attributes during the production process with an RPN value of 294 and workers did not pay attention to pressing time with an RPN value of 252. FTA analysis results shows two basic causes of problem, namely workers do not use PPE (Personal Protective Equipment) with a probability of 0.24 and that no tools are available to measure standard time with a probability of 0.2. The proposed improvements implemented by observing the GMP aspect (Good Manufacturing Practice) are to use digital timer, make a tool cleaning form, and make hand-washing posters, smoke free, a restriction on eating and drinking. There is a descrease in the value of DPMO to 16500 with sigma level of 3.6321 after implementation. Keywords: failure mode and effect analysis, fault tree analysis, good manufacturing practice, tofu factory